The Effect of Organizational Forces on Individual Morality: Judgment, Moral Approbation, and Behavior - Jones, Thomas M. (Business ethics quarterly, 1998)
To date, our understanding of ethical decision making and behavior in organizations has been concentrated in the area of moral judgment, largely because of the hundreds of studies done involving cognitive moral development. This paper addresses the problem of our relative lack of understanding in other areas of human morality by applying a recently developed construct—moral approbation—to illuminate the link between moral judgment and moral action. This recent work is extended here by exploring the effect that organizations have on ethical behavior in terms of the moral approbation construct.